Endosulfan upregulates AP-1 binding and ARE-mediated transcription via ERK1/2 and p38 activation in HepG2 cells - Song, Min Ok; Lee, Chang-Ho; Yang, Hyun Ok; Freedman, Jonathan H. (ELSEVIER IRELAND LTD, 2012)
Endosulfan is an organochlorine insecticide and has been implicated in neurotoxicity, hepatotoxicity, immunosuppression and teratogenicity. However, the molecular mechanism of endosulfan toxicity is not yet clear. Recent studies demonstrated that oxidative stress induced by endosulfan is involved in its toxicity and accumulating evidence suggests that endosulfan can modulate the activities of stress-responsive signal transduction pathways including extracellular signal regulated kinases (ERK) 1/2. However, none of the previous studies investigated the ability of endosulfan to modulate activating protein-1 (AP-1) binding and antioxidant response element (ARE)-mediated transcription as an underlying mechanism of endosulfan toxicity. In this report, we show that treatment of HepG2 cells with endosulfan significantly increased oxidative stress-responsive transcription via AP-1 activation. In addition, endosulfan-induced transcription was enhanced in cells depleted of glutathione by buthionine sulfoximine (BSO) treatment. Exposure to endosulfan resulted in a significant increase in the activities of MAPKs, ERK1/2 and p38. Endosulfan-induced increases in enzymatic activities of these MAPKs were consistent with MAPK phosphorylation. Endosulfan exposure also caused an increase in c-Jun phosphorylation. These results suggest a model for endosulfan toxicity in which endosulfan increases ERK1/2 and p38 activities and these activated MAPKs then increase c-Jun phosphorylation. Phosphorylated c-Jun, in turn, increases AP-1 activity, which results in activation of ARE-mediated transcription. (C) 2011 Elsevier Ireland Ltd. All rights reserved.
Keywords: DRUG-METABOLIZING-ENZYMES; HUMAN HACAT KERATINOCYTES; MAP KINASE PATHWAYS; GENE-EXPRESSION; C-JUN; LIPID-PEROXIDATION; PROTEIN-KINASES; REACTIVE OXYGEN; IN-VITRO; ORGANOCHLORINE INSECTICIDES